(untitled) (Fiep Bulletin - online, 2016)
The lack of investment and systematic and continuous actions in promoting quality of life has been responsible for the costly and growing absenteeism costs, presenteeism and turnover, as well as compromising productivity in the workplace. The aim of this experimental study was to analyze what are the main causes of absenteeism in the garment industry of the western region of Paraná formed by employees of the court-fashion sector, consisting of a large majority of women. It was applied to the Evaluation System Research Lifestyle and worker productivity (SAEVP), being a private research where the employee answers 25 questions seeking business indicators related to preventive behavior, physical activity, nutrition, stress perception, sleep and current level of health, alcohol intake, tobacco, relationships, and willingness to work. We found that 48.28% did not do physical activity during leisure time, 75.86% exposed to the sun without protection, 16.38% negative perception of stress management, 27.59% negative perception of health. When asked about the perception of work 30 days 3-7 days we found that 32.76% moved away because of illness, 55.17% did not feel like going to work, 62.02% felt unwell and hopeless and 64.66% felt pain or discomfort when performing tasks. Therefore, we performed a study of medical certificates in the period from January 6 to 30 April 2015, found up 1244 medical certificates, 181 employees on leave during this period. The most common presence in the medical certificates were muscular aches and discomforts 21.20%. The cost of absenteeism was R 135,709.00 for the company. We conclude that it is necessary to further study and implementation of quality of life programs that will contribute to the health and welfare of the worker, in order to reduce absenteeism and presenteeism.